Modulation of Spin Dynamics via Voltage Control of Spin‐Lattice Coupling in Multiferroics. (3rd February 2017) - Zhu, Mingmin; Zhou, Ziyao; Peng, Bin; Zhao, Shishun; Zhang, Yijun; Niu, Gang; Ren, Wei; Ye, Zuo‐Guang; Liu, Yaohua; Liu, Ming
Abstract : Motivated by the most recent progresses in both magnonics (spin dynamics) and multiferroics fields, this work aims at magnonics manipulation by the magnetoelectric coupling effect. Here, voltage control of magnonics, particularly the surface spin waves, is achieved in La0.7 Sr0.3 MnO3 /0.7Pb(Mg1/3 Nb2/3 )O3 ‐0.3PbTiO3 multiferroic heterostructures. With the electron spin resonance method, a large 135 Oe shift of surface spin wave resonance (≈7 times greater than conventional voltage‐induced ferromagnetic resonance shift of 20 Oe) is determined. A model of the spin‐lattice coupling effect, i.e., varying exchange stiffness due to voltage‐induced anisotropic lattice changes, has been established to explain experiment results with good agreement. Additionally, an "on" and "off" spin wave state switch near the critical angle upon applying a voltage is created. The modulation of spin dynamics by spin‐lattice coupling effect provides a platform for realizing energy‐efficient, tunable magnonics devices. Abstract : Magnonics manipulation by the magnetoelectric coupling effect is of great importance in voltage‐tunable spin wave applications. Voltage control of spin wave resonance as well as critical angle has been demonstrated in La0.7 Sr0.3 MnO3 /0.7Pb(Mg1/3 Nb2/3 )O3 ‐0.3PbTiO3 multiferroic heterostructures. We related this effect to the spin‐lattice coupling, which varies exchange stiffness due to voltage‐induced anisotropic lattice changes.